Crystallization history of enriched shergottites from Fe and Mg isotope fractionation in olivine megacrysts. (15th June 2017) - Collinet, Max; Charlier, Bernard; Namur, Olivier; Oeser, Martin; Médard, Etienne; Weyer, Stefan
Abstract: Martian meteorites are the only samples available from the surface of Mars. Among them, olivine-phyric shergottites are basalts containing large zoned olivine crystals with highly magnesian cores (Fo 70–85) and rims richer in Fe (Fo 45–60). The Northwest Africa 1068 meteorite is one of the most primitive "enriched" shergottites (high initial 87 Sr/ 86 Sr and low initial ε 143 Nd). It contains olivine crystals as magnesian as Fo 77 and is a major source of information to constrain the composition of the parental melt, the composition and depth of the mantle source, and the cooling and crystallization history of one of the younger magmatic events on Mars (∼180 Ma). In this study, Fe-Mg isotope profiles analyzed in situ by femtosecond-laser ablation MC-ICP-MS are combined with compositional profiles of major and trace elements in olivine megacrysts. The cores of olivine megacrysts are enriched in light Fe isotopes ( δ 56 FeIRMM-14 = −0.6 to −0.9‰) and heavy Mg isotopes ( δ 26 MgDSM-3 = 0–0.2‰) relative to megacryst rims and to the bulk martian isotopic composition ( δ 56 Fe = 0 ± 0.05‰, δ 26 Mg = −0.27 ± 0.04‰). The flat forsterite profiles of megacryst cores associated with anti-correlated fractionation of Fe-Mg isotopes indicate that these elements have been rehomogenized by diffusion at high temperature. We present a 1-D model of simultaneous diffusion and crystal growth that reproduces the observed element and isotope profiles. The simulation results suggest that the cooling rate during megacryst core crystallization was slow (43 ± 21 °C/year), and consistent with pooling in a deep crustal magma chamber. The megacryst rims then crystallized 1–2 orders of magnitude faster during magma transport toward the shallower site of final emplacement. Megacryst cores had a forsterite content 3.2 ± 1.5 mol% higher than their current composition and some were in equilibrium with the whole-rock composition of NWA 1068 (Fo 80 ± 1.5). NWA 1068 composition is thus close to a primary melt (i.e. in equilibrium with the mantle) from which other enriched shergottites derived.